Randomised trial and open-label extension study of an anti-interleukin-6 antibody in Crohn's disease (ANDANTE I and II). Issue 1 (15th December 2017) - Danese, Silvio; Vermeire, Séverine; Hellstern, Paul; Panaccione, Remo; Rogler, Gerhard; Fraser, Gerald; Kohn, Anna; Desreumaux, Pierre; Leong, Rupert W; Comer, Gail M; Cataldi, Fabio; Banerjee, Anindita; et al.
Abstract : Objective: Neutralising pro-inflammatory interleukin-6 (IL-6) may effectively treat Crohn's disease (CD). Effects of PF-04236921, an anti-IL-6 antibody, in adults with CD are reported. Design: Parallel-group, dose-ranging, double-blind trial with 4-week screening and 12-week treatment periods. After induction, patients entered 28-week follow-up or 48-week open-label extension (OLE) with 28-week follow-up. Adults with confirmed CD and inadequate response to anti-tumour necrosis factor (TNF) therapy were included. Induction study : 249 patients randomised 1:1:1:1 to placebo, PF-04236921 10, 50 or 200 mg by subcutaneous injection on days 1 and 28. OLE study : PF-04236921 50 mg every 8 weeks up to six doses followed by 28-week follow-up. Results: 247 patients were randomised and received treatment in the induction study. The 200 mg dose was discontinued due to safety findings in another study (NCT01405196 ) and was not included in the primary efficacy analysis. Crohn's Disease Activity Index (CDAI)-70 response rates with PF-04236921 50 mg were significantly greater than placebo at weeks 8 (49.3% vs 30.6%, P<0.05) and 12 (47.4% vs 28.6%, P<0.05) and met the primary end point. Week 12 CDAI remission rates with PF-04236921 50 mg and placebo were 27.4% and 10.9%, respectively (16.5% difference; P<0.05). 191 subjects received treatment in the OLE. Common treatment-emergent and serious adverse events in both studies included worsening CD, abdominal pain and nasopharyngitis. Conclusions: PF-04236921 50 mg induced clinical response and remission in refractory patients with moderate-to-severe CD following failure of anti-TNF therapy. GI abscess and perforation were observed, a specific focus of attention during future clinical development. Trial registration number: NCT01287897 and NCT01345318 .